Depression, anxiety and stress in adult children caregivers of oncological patients - Teixeira, Ricardo João (2018)
Te aim of this study is to describe levels of depression, anxiety, and stress in adult ofspring of cancer patients; and to analyze gen der diferences in psychological morbidity, as well as the association between psychological morbidity and traumatic symptomatology. Tis study is correlational with a sample of 214 adult ofspring who completed the Depression, Anxiety and Stress Scales (DASS-21) and the Impact of Event Scale-Revised (IES-R). Te results revealed that 6-60% of the participants showed ‘normal’ or ‘mild’ levels of stress, anxiety, or depression; 15-26% ‘moderate’ levels; and 4-12% ‘severe’ or ‘extremely severe’ levels. Women had higher levels of anxiety and stress than men. Positive correlations were found between the DASS 21 and the IES-R. In conclusion, some adult ofspring caregivers re veal severe levels of psychological morbidity. Te results show a need for psychological intervention in this population, particularly in the female gender.